2018
DOI: 10.3899/jrheum.180135
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome in Gut and Joint Inflammation in Psoriatic Arthritis and Spondyloarthritis

Abstract: Spondyloarthritis (SpA) encompasses a group of diseases characterized by an inflammatory arthritis involving both joints and entheses. However, extraarticular symptoms constitute a large element of the pathology and should not be underestimated. Microscopic gut inflammation is observed in 50% of patients with SpA and has been linked to disease activity, underscoring the effect of gut inflammation in SpA. In this review, we discuss the influence of gut microbiota on SpA pathogenesis. A change in microbiota comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…There have been some studies too which have examined changes in microbiome and onset of PsA 46 which to date have been inconclusive. This is clearly an area for further research focus as microbial-driven populations of IL17-producing innate immune cells have been identified in other tissues 47 and a recent study very nicely demonstrated the considerable influence of the gut microbiota-together and over time-on systemic immune cell dynamics.…”
mentioning
confidence: 99%
“…There have been some studies too which have examined changes in microbiome and onset of PsA 46 which to date have been inconclusive. This is clearly an area for further research focus as microbial-driven populations of IL17-producing innate immune cells have been identified in other tissues 47 and a recent study very nicely demonstrated the considerable influence of the gut microbiota-together and over time-on systemic immune cell dynamics.…”
mentioning
confidence: 99%
“…At the same time, there was an increase in the number of Dialister flora in ileal and colon biopsies of AS patients, which was positively correlated with AS disease activity score. 46 Intestinal T lymphocytes activated by intestinal pathogenic microbial antigens migrate to joints and induce inflammation. 47 In the inflammatory state, the release of various cytokines will cause vasodilation and increase vascular permeability, resulting in increased leukocyte infiltration.…”
Section: Intestinal Flora Regulation Mechanism Of Moxibustion In Anky...mentioning
confidence: 99%
“…Nonetheless, the increased severity and frequency of tarsitis in developed countries is probably associated with a higher incidence of intestinal infections. The relationship between gut inflammation and arthritis or enthesitis is a challenging research topic that includes intestinal dysbiosis and cell migration (120)(121)(122). It has been suggested that some inflammatory mediators like cytokines and leukocytes can be originated in the gut, and such could be the case of ILC3 cells (104) or Tγδ cells (123).…”
Section: Inflammatory Pathways In Axial and Peripheral Spamentioning
confidence: 99%